Cognitive and mood effects of phenobarbital treatment in people with epilepsy in rural China: a prospective study. Issue 12 (31st July 2012) - Ding, Ding; Zhang, Qing; Zhou, Dong; Lin, Weihong; Wu, Qingsheng; Sun, Jixin; Zhao, Qianhua; Yu, Peimin; Wang, Wenzhi; Wu, Jianzhong; Bell, Gail S; Kwan, Patrick; et al.
Abstract : Background: Phenobarbital is an effective treatment for epilepsy but concerns remain over its potential neurocognitive toxicity. This prospective study evaluated the effects of phenobarbital treatment on cognition and mood in people with epilepsy in rural China. Methods: We recruited 144 adults with convulsive seizures and 144 healthy controls from six sites in rural China. People with epilepsy were treated with phenobarbital monotherapy for 12 months. At baseline, and at 3, 6 and 12 months, cases and controls were evaluated with a battery of neuropsychological tests: the Mini-Mental State Examination, the Hamilton Depression Rating Scale, a digit span test, a verbal fluency test, an auditory verbal learning test and a digit cancellation test. Efficacy of phenobarbital treatment was evaluated at the end of follow-up for those with epilepsy. Results: Cognitive test scores and mood ratings were available for 136 (94%) people with epilepsy and 137 (95%) controls at the 12 month follow-up. Both groups showed slightly improved performance on a number of neuropsychological measures. The people with epilepsy showed greater performance gains (p=0.012) in verbal fluency. Nine people with epilepsy complained of memory problems during the treatment period. Conclusion: In this study, phenobarbital was not found to have a major negative impact on cognitive function of people with convulsive seizures and some cognitive gains were observed, possibly due to improved seizure control.